Integration of Nursing Education and Service: A Pragmatic Model to Empower Nurses and Inform Healthcare Policy in India - Nipin Kalal; Suresh K. Sharma (Journal of Integrated Health Sciences, 2025)
The integration of nursing education and service stands as a critical imperative for addressing the multifaceted challenges within India’s healthcare system. As of now, India has not implemented this practice, and there is no explicit policy provided by the government. The proposed project aims to assess the concept of integration in nursing, empowering nurses to take on diverse responsibilities within healthcare settings. The SWOT and PESTEL analyzed along with using available literature, expert suggestions, and relevant documents. Integrating nursing education and service offers potential benefits in skill enhancement, improved patient care, and resource optimization, empowering nurses. This innovative model, if successfully implemented, not only addresses the traditional dichotomy between theoretical learning and practical application but also cultivates a workforce of nurses equipped to navigate the complexities of contemporary health care.